(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research were: to synthesize components, to develop, and study the usage of the blended instructional system model by problem-based learning for enhancing the problem-solving ability of secondary school students. The research methodology was divided into three phases. Phase I: surveying present needs and problems in mathematics teaching for teachers and Mattayom 6 students. The model’s elements were evaluated by experts. The tools were questionnaire, interview form and model’s elements assessment form. Phase II: developing the model and confirming the model. The tools were the draft of the model, courseware, and assessment forms. Phase III: evaluating the effects of using the implemented model. The samples were 36 students in Mathayom 6. The statistics were percentage, means, standard deviation, and t-test dependent. The results are as follows: 1) The teaching model consists of 3 stages. (1) Input consists of 1) Knowledge Linking theory 2) design, selection, and application of integrated learning management techniques; 3) problem-based learning management; (2) Processes include learning management, integrated instructional model, problem-based learning. In order to promote problem-solving ability six steps are implemented: PLACRE 1) Preparation for learning 2) Learn & Link 3) Action 4) Conclusion 5) Reflection 6) Evaluation and the last stage, (3) Output (1) The effectiveness of learning model was 78.15 / 78.04 for the criterion was 75/75 and the learning effectiveness index was 0.5589. (2) The problem-solving ability was higher than the pre-learning level at the .05 level. The learning achievement of the students learning through the instructional model was higher than before the study at the .05 level. The students were satisfied with the learning through the model at a high level.